Saifiddin Bokharzi - A Thug Who Developed The Teaching Of Kubravia - Fayzulloyevna, Norova (Indonesian Journal Publisher, 2025)
In this article, the teaching of Najmuddin Kubro, who is the representative of Kubravian teachings of Saifiddin Boharzi, and his relationship with him are highlighted. Also, the article describes the details of chilling in the works of Saifiddin Boharzi